PROGRAM PEMBERDAYAAN EKONOMI MUALAF: STUDI KASUS PROGRAM KAMPUNG INSPIRATIF DAN MANDIRI DESA KLEPU OLEH LMI - Muhammad Affan Satria; A. Syifa'ul Qulub (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to understand the role of LMI in Klepu’s muslim convert economic empowerment. This research is a descriptive qualitative study using a case study method. The data in this study were obtained through interviews with program manager of LMI in Madiun, the assistant of the local community, and also the recipients of the program. The results of this study indicate that LMI has a role in economic empowerment of Klepu’s muslim convert, including: as a community facilitator, as a liaison or support between economically supported Muslims with the help of converts who are one of the groups who can receive zakat; utilize existing resources and skills in Klepu Village; To support the agreement of stakeholders, LMI; and providing skills training needed by recipients of the LMI program in Klepu Village.Keywords: Klepu’s Muslim Convert, LMI, economic empowermentREFERENCESAlfian. 2015. Islam Indonesia dan Dakwah Islam Kekinian. Jakarta: Bintang PustakaBadan Pusat Statistik. 2014. Demografi Kebaputen Ponorogo. PonorogoBAZNAS. 2017. Kaji Dampak Penyaluran Zakat BAZNAS Terhadap Kesejahteraan Mustahik Tahun 2016. Jakarta________. 2018. Indeks Rawan Pemurtadan : Konsep dan Implementasi Pengukuran. JakartaDesa Klepu. 2016. Rencana Pembangunan Jangka Menengah Desa. Ponorogo. Jawas, Yazid Abdul. 2014. Kiat-Kiat Islam Mengatasi Kemiskinan. Bogor: Pustaka At TaqwaKBBI Daring. 2018. “Kamus Besar Bahasa Indonesia Daring”, pada https://kbbi.kemdikbud.go.id, diakses pada 17 September 2018 pukul 20.35Lembaga Manajemen Infaq. 2016. Assesment Desa Klepu. MadiunMawardi, Imron dan Widiastuti Tika. 2015. Kesejahteraan Dan Kemiskinan Dalam Perspektif Islam. Surabaya : STAINA PressNeuman, Lawrence. 2006. Social Research Methods : Qualitative and Quantitative Approaches (6 ed.). New Delhi: Pearson Education CompanySalim, Kamal Sayyid. 2010. Shahih Fiqih. Jakarta: Ensiklopedi FiqhSugiyono. 2017. Metode Penelitian Kualitatif. Bandung: Alfabeta.